2013
DOI: 10.1111/trf.12291
|View full text |Cite
|
Sign up to set email alerts
|

Nitroprusside inhibits calcium‐induced impairment of red blood cell deformability

Abstract: Our results suggest that nitroprusside treatment of RBCs may protect them from intracellular calcium increase-mediated stiffness, which may occur during microvascular perfusion in diseased states, as well as during RBC storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 45 publications
(78 reference statements)
4
51
2
2
Order By: Relevance
“…In addition, calcium leak leads to membrane lipid asymmetry with exposure of phosphatidylserine on the surface of RBCs which contributes to increased adhesivity of sickle RBCs [70], [71]. These same phenomena can be recapitulated in normal RBCs using calcium ionophores [66], [70], [72]. Thus, inhibiting the Gardos channel has been a major therapeutic target in treating SCD as it would improve RBC deformability, decrease RBC adhesion, and decrease sickling [73].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, calcium leak leads to membrane lipid asymmetry with exposure of phosphatidylserine on the surface of RBCs which contributes to increased adhesivity of sickle RBCs [70], [71]. These same phenomena can be recapitulated in normal RBCs using calcium ionophores [66], [70], [72]. Thus, inhibiting the Gardos channel has been a major therapeutic target in treating SCD as it would improve RBC deformability, decrease RBC adhesion, and decrease sickling [73].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study using inhaled NO showed promise in reducing pain crises [95], but the study was small. Despite potential of NO to relieve multiple symptoms of SCD (as demonstrated by us and others [36], [37], [38], [39], [40], [42], [66], [72], [88]), successful translation has been elusive. However, it is important to note that not all NO congeners are the same and nitrite has several properties that make it more promising than other agents: (1) nitrite targets NO activity to hypoxic areas where it is most needed [88] (unlike other agents like NO inhalation that targets the lungs and sGC activators which have systemic activity), (2) nitrite can be delivered to produce NO activity chronically with potential for constantly elevated levels achieved through the nitrate-nitrite-NO cycle [74].…”
Section: Discussionmentioning
confidence: 99%
“…During storage, erythrocyte membrane permeability to calcium (Ca 2+ ) ions increases over time, leading to increased intracellular Ca 2+ levels. Intracellular Ca 2+ activates calcium-sensitive KCa3.1 ion channels, which are located in the erythrocyte membrane 35 . The resulting potassium ion efflux causes RBCs to shrink and makes their cell membranes less flexible 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The resulting potassium ion efflux causes RBCs to shrink and makes their cell membranes less flexible 36 . Previous studies showed that nitric oxide has a crucial role in enhancing RBC deformability and that reduced RBC nitric oxide levels decrease deformability 35,37 . Loss of RBC deformability may lead to an increased rate of intravascular hemolysis and a reduced lifespan of transfused stored RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced intracellular calcium has several effects that can affect deformability. This includes activation of the Gardos channel resulting in leakage of potassium from the RBC affecting cation homeostasis (Ney et al, 1990; Barodka et al, 2013a) causing shrinkage of the cell and impaired deformability. Calcium also activates calpain that can degrade additional proteins on the membrane (Redding et al, 1991).…”
Section: Introductionmentioning
confidence: 99%